Cannabinoid receptor agonist attenuates angiotensin II–induced enlargement and mitochondrial dysfunction in rat atrial cardiomyocytes - Altieri, Danielle I.; Etzion, Yoram; Anderson, Hope D. (Frontiers in Pharmacology, 2023)
Pathological remodeling of atrial tissue renders the atria more prone to arrhythmia upon arrival of electrical triggers. Activation of the renin-angiotensin system (RAS) is an important factor that contributes to atrial remodeling, which may result in atrial hypertrophy and prolongation of P-wave duration. In addition, atrial cardiomyocytes are electrically coupled via gap junctions, and electrical remodeling of connexins may result in dysfunction of coordinated wave propagation within the atria. Currently, there is a lack of effective therapeutic strategies that target atrial remodeling . We previously proposed that cannabinoid receptors (CBR) may have cardioprotective qualities. CB13 is a dual cannabinoid receptor agonist that activates AMPK signaling in ventricular cardiomyocytes. We reported that CB13 attenuates tachypacing-induced shortening of atrial refractoriness and inhibition of AMPK signaling in the rat atria. Here, we evaluated the effects of CB13 on neonatal atrial rat cardiomyocytes (NRAM) stimulated by angiotensin II (AngII) in terms of atrial myocyte enlargement and mitochondrial function. CB13 inhibited AngII-induced enhancement of atrial myocyte surface area in an AMPK-dependent manner. CB13 also inhibited mitochondrial membrane potential deterioration in the same context. However, AngII and CB13 did not affect mitochondrial permeability transition pore opening. We further demonstrate that CB13 increased Cx43 compared to AngII-treated NRAM. Overall, our results support the notion that CBR activation promotes atrial AMPK activation, and prevents myocyte enlargement (an indicator that suggests pathological hypertrophy), mitochondrial depolarization and Cx43 destabilization. Therefore, peripheral CBR activation should be further tested as a novel treatment strategy in the context of atrial remodeling.